Study on MHD Boundary Layer Flow of Combined Heat and Mass Transfer Over a Moving Inclined Plate in a Porous Medium With Suction and Viscous Dissipation in Presence of Hall Effect - Ali, Mohammad; Alam, Mohammad Shah (Engineering International, 2014)
The Hall effects on the steady MHD boundary layer flow of an incompressible fluid of combined heat and mass transfer over a moving inclined plate in a porous media with suction and viscous dissipation has studied. An external magnetic field is applied perpendicular to the surface and the fluid motion is subjected to a uniform suction and injection. A closed form solutions of the equations governing the flow are obtained for the velocity, secondary velocity, and temperature and concentration profiles. The dimensionless governing equations are solved using R-K method along with shooting technique. The velocities, temperature and concentration profiles are presented graphically for different values of governing flow parameters. The results presented graphically illustrate that primary velocity field decrease due to increase of magnetic parameter, angle of inclination, permeability parameter and suction parameter while secondary velocity also decrease for magnetic parameter, Hall parameter and permeability parameter .Other parameters increase the velocities of the fluid flow. Temperature field increases in the presence of Magnetic parameter, Grashof number, Modified Grashof number and permeability parameter and decreases for Prandlt number and suction parameter. Also, concentration profiles decreases for increasing the values of magnetic parameter, Hall parameter, Schmid number and suction parameter but there is no effect on concentration of the remaining parameters. Also the skin friction coefficient, the local Nusselt number and the local Sherwood number are presented in Tables 1-3.